IDIOSYNCRATIC VOLATILITY AND HERD BEHAVIOR: INDONESIA STOCK MARKET CASE - Buddi Wibowo (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2019)
Anomalies revealed by various research of asset pricing models indicate the presence of other risk factors which have not been included in the model. Even the most recent models such as the Fama-French Five Factor still leave several other risk factors included in the error terms produced by the model. An empirical test that tests whether this idiosyncratic risk significantly affects stock returns becomes necessary and urgent in order to obtain a solid theoretical understanding. Empirical tests in emerging market stock markets such as the Indonesia stock exchange are important in sharpening and enriching the understanding of idiosyncratic risk because transactions in emerging market stock markets are more likely to be influenced by the existence of herding behavior where foreign investors or large investors can often direct trading in several stocks. The empirical test of the idiosyncratic risk and herd behavior correlation in the Indonesia stock exchanges shows herd behavior, especially in stocks that have high idiosyncratic risk and occur in the normal period, not in the crisis period. Herd behavior still avoids too much risk taking, as in times of high uncertainty such as during the crisis period.